Co-operation in the supermarket aisle: young children's accounts of family food shopping. Issue 11 (25th November 2014) - de Faultrier, Brigitte; Marshall, David
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Children are increasingly seen as active consumers participating in various aspects of family food consumption. The purpose of this paper is to look at children's first-hand accounts of their visits to the supermarket and reports on their in store experiences as participants in the family food shopping. It offers an account of family food shopping from the perspective of the children. Design/methodology/approach – Qualitative discussion groups with children aged eight to 11 years research were used to elicit children's perceptions of food shopping as part of a study into food consumption experiences. This offers an opportunity to capture the children's perspective on this everyday consumption activity. Findings – Engaging in family food shopping is part of a socialisation process that introduces children to food retail environments and to shopping scripts played out in store. Young children claim to actively participate in family food shopping in store contributing in a variety of ways to family food purchases that includes making requests in store, negotiating over product choices and assisting with the food shopping. The strategies employed by the children include restricting requests to specific product categories (usually for sweets, or cereals or products for their school lunchbox); selecting products on behalf of other family members; dissuading parents for buying certain food items and helping out in store. Most of the first-hand accounts reflect a positive experience with children contributing to the food decisions that relate directly to their interests. The research finds relatively little conflict and more co-operation between children and their parents in an attempt to influence what goes into the shopping trolley. Research limitations/implications – This is a small exploratory study with a geographically constrained sample. The children's accounts cannot be verified but are presented as a way of looking at how children themselves relate to the family food shopping experience. Future research might extend the geographical scope of this investigation and consider soliciting parental views to validate the children's accounts. Practical implications – This work provides further evidence of the ways in which children are actively included as part of family food decisions in a supermarket context. Children's in store contributions to family food can inform retailers and companies as well as policy makers. Originality/value – This offers a unique insight into how children view shopping with the family and relates more broadly to the discussion around children's consumption and their role as active consumers.